Identifying urotropine derivatives as co-donors of formaldehyde and nitric oxide for improving antitumor therapy. Issue 61 (12th July 2021) - Zhang, Yu; Feng, Shujun; Meng, Xia; Luo, Jun; Xu, Yurui; Ning, Xinghai
Abstract : The first co-donor of formaldehyde and nitric oxide (FANO) was synthesized via pharmacophore integration strategy, which simultaneously generated NO and formaldehyde on-demand, resulting in synergistic anticancer effects both in vitro and in vivo . Abstract : A pharmacophore integration strategy was utilized to develop the first co-donor of formaldehyde and nitric oxide (FANO), composed of urotropine derived nitramine/nitrosamine. FANO simultaneously generated formaldehyde and nitric oxide on-demand, resulting in synergistic anticancer effects. Importantly, liposomal formulation of FANO effectively inhibited tumor growth with minimal side-effects, providing a potent combined nitric oxide therapy for malignancy.